2017
DOI: 10.21276/aabs.1460
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Interface dermatitis : An Observational study'

Abstract: Background: Major role of a dermatopathologists is to try to make specific diagnosis of inflammatory skin diseases. IFD means inflammatory infiltrate that abuts or obscures the dermo-epidermal junction in askin biopsy.This type of reaction is also seen in skin disorders associated with systemic illness like LE and skin changes of potentially fatal disorders such as Graft versus host disease, S-J syndrome and toxic epidermal necrolysis. Results: In the present study, a total of 121 cases of IFD were studied, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…6,8 Female preponderance was noted in the studies done by Kumar et al (57.78%), Pawar et al (59.9%), Dhar et al (58.60%) and Hegde et al (57.6%). 5,[9][10][11] Studies on lichen planus by Kumar et al showed a ratio of 60% males and 40% females, Kachhawa et al with 58.6% males and 41.3% females. 12,13 The chief complaints in our study group were pruritic skin lesions in majority -27 of 43 cases (62.80%) followed by alopecia in 7 cases (16.30%).…”
Section: List Of Discordant Casesmentioning
confidence: 99%
“…6,8 Female preponderance was noted in the studies done by Kumar et al (57.78%), Pawar et al (59.9%), Dhar et al (58.60%) and Hegde et al (57.6%). 5,[9][10][11] Studies on lichen planus by Kumar et al showed a ratio of 60% males and 40% females, Kachhawa et al with 58.6% males and 41.3% females. 12,13 The chief complaints in our study group were pruritic skin lesions in majority -27 of 43 cases (62.80%) followed by alopecia in 7 cases (16.30%).…”
Section: List Of Discordant Casesmentioning
confidence: 99%